The 'price signal' for health care is loud and clear: A cross‐sectional study of self‐reported access to health care by disadvantaged Australians. (29th June 2015) - Paul, Christine; Bonevski, Billie; Twyman, Laura; D'Este, Catherine; Siahpush, Mohammad; Guillaumier, Ashleigh; Bryant, Jamie; Fradgley, Elizabeth; Palazzi, Kerrin
Abstract: Objective: To describe self‐reported inability to access health care and factors associated with lack of access among a socioeconomically disadvantaged group. Method: A cross‐sectional survey with 906 adult clients of a large community welfare agency in New South Wales. Clients attending the service for emergency assistance completed a touchscreen survey. Results: Inability to access health care in the prior year was reported by more than one‐third of the sample (38%), compared to the 5% found for the general population. Dentists (47%), specialists (43%) or GPs (29%) were the least accessible types of health care. The main reason for inability to access health care was cost, accounting for 60% of responses. Almost half (47%) the sample reported delayed or non‐use of medicines due to cost. Increasing financial stress was associated with increased inability to access GP or specialist care, medicines and imaging. Higher anxiety scores were associated with inability to access health care, and with cost‐related inability to access medicines and imaging. Conclusion: For disadvantaged groups, cost‐related barriers to accessing care are prominent and are disproportionately high – particularly regarding dentistry, specialist and GP care. Implications: Improvements in health outcomes for disadvantaged groups are likely to require strategies to reduce cost‐related barriers to health care.